Diazaisoindigo bithiophene and terthiophene copolymers for application in field‐effect transistors and solar cells. Issue 16 (10th June 2017) - Yue, Wan; Li, Cheng; Tian, Xuelin; Li, Weiwei; Neophytou, Marios; Chen, Hu; Du, Weiyuan; Jellett, Cameron; Chen, Hung‐Yang; Onwubiko, Ada; McCulloch, Iain
ABSTRACT: Two donor–acceptor conjugated polymers with azaisoindigo as acceptor units and bithiophene and terthiophene as donor units have been synthesized by Stille polymerization. These two polymers have been successfully applied in field‐effect transistors and polymer solar cells. By changing the donor component of the conjugated polymer backbone from bithiophene to terthiophene, the density of thiophene in the backbone is increased, manifesting as a decrease in both ionization potential and in electron affinity. Therefore, the charge transport in field‐effect transistors switches from ambipolar to predominantly hole transport behavior.PAIIDTT exhibits hole mobility up to 0.40 cm 2 /Vs and electron mobility of 0.02 cm 2 /Vs, whereasPAIIDTTT exhibits hole mobility of 0.62 cm 2 /Vs. Polymer solar cells were fabricated based on these two polymers as donors with PC61 BM and PC71 BM as acceptor wherePAIIDTT shows a modest efficiency of 2.57% with a very low energy loss of 0.55 eV, whilePAIIDTTT shows a higher efficiency of 6.16% with a higher energy loss of 0.74 eV. Our results suggest that azaisoindgo is a useful building block for the development of efficient polymer solar cells with further improvement possibility by tuning the alternative units on the polymer backbone. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2691–2699 Abstract : Azaisoindigo bithiophene and terthiophene polymers have been synthesized. Their charge transport properties for thin‐film transistors have been investigated, and the azaisoindigo‐based polymers for solar cells application were first extended. The thiophene density along the backbones can effectively influence the charge transport property as well as the photovoltaic performance of conjugated polymers.